Polyamorphism and Two State Model in Liquid GeO\(_{2}\) under Compression: Insight from Visualization of Molecular Dynamics Data - Hong, Nguyen Van; Lan, Mai Thi; Nhan, Nguyen Thu (Communications in Physics, 2014)
The polyamorphism and two-state model based on the coordination number distribution in liquid GeO\(_{2}\) at 3200~K and in a wide pressure range are investigated by molecular dynamics simulation. Results show that the structure of liquid GeO\(_{2}\) mainly consists of GeO\(_{x}\) coordination units \((x=4,5,6)\) and OGe\(_{y}\) linkages \((y=2, 3)\). The distribution of OGe\(_{y}\) linkages in network structure is not uniform but tends to form clusters of OGe\(_{y}\). The cluster of OGe\(_{2}\) will form low-density phase region, conversely the cluster of OGe\(_{3}\) will form high-density phase region. In other word, under compression, in the liquid GeO\(_{2}\) coexist two states: low-density and high-density. The size of phase regions significantly depends on compression.